OnlineLino—A Website on Architect Raul Lino’s Built Heritage at Médio Tejo, in Portugal - Anabela Moreira; Inês Serrano; Paulo Santos; Regina Delfino; Pedro Matos; Ana Gracio; Ana Xavier (Buildings)
The cultural context and values of twentieth-century architecture and construction confirm the need to preserve them for future generations, given the multiple challenges to overcome. Raul Lino da Silva (1879–1974) is a celebrated Portuguese architect who worked throughout the twentieth century and whose architectural legacy is scattered from the north to the south of the country. The aim of this paper is to present the development of the website OnlineLino, which is related to the architectural and construction heritage of Raul Lino in the Médio Tejo region, an inland Portuguese territory with low demographic density. This work is focused on integrating documentary information dispersed across different digital funds, by aggregating it on a website that will be made available for public access in the future. To this end, data were collected from different funds, and the information was aggregated and systematised so that it could be included in the digital database developed, the OnlineLino website. The work was carried out by a multidisciplinary team in an academic setting, involving the areas of architecture, civil engineering, computer engineering and design. We hope that this website will contribute to the dissemination of Raul Lino’s architectural legacy, especially for buildings that are less studied and known.